Pengaruh adiksi internet terhadap kecerdasan emosi pada siswa di SMK Muhammadiyah Sangasanga - Dwirahmadani, Putri; Purnamasari, Desti (Fakultas Psikologi Universitas Hang Tuah, 2025)
The growing phenomenon of internet use among students has brought both positive and negative impacts on their lives. One of the negative impacts that has begun to emerge is internet addiction, which is characterized by excessive use that interferes with social and emotional aspects. Students experiencing internet addiction are suspected to have lower emotional management abilities. This study aims to determine the influence of internet addiction on emotional intelligence among students at SMK Muhammadiyah Sangasanga. The research employed a quantitative method with simple linear regression analysis. The subjects consisted of 226 students selected through total sampling technique. The instruments used were the Internet Addiction Scale (18 items) and the Emotional Intelligence Scale (26 items). The results showed a significant negative effect of internet addiction on emotional intelligence, with a regression coefficient of -0.718 and a significance value of 0.000 (p < 0.05). The R Square value of 0.430 indicates that 43% of the variance in emotional intelligence is influenced by internet addiction. Thus, the higher the level of internet addiction, the lower the level of emotional intelligence among students.